Biochemical Composition and Nutrient Profilling of Selected Brown Seaweeds from West Coast of India - Itishree Das; A.K.Balange; Layana P.; Martin Xavier K.A; G.Deshmukhe (Journal of Indian Fisheries Association, 2022)
Seaweeds have been employed in human and animal diets for centuries. Their nutrient content varies according to the species, seasons, and geographical location. Very little information is available on biochemical properties of the seaweeds from the Maharashtra coast. Thus, in the current study, different species of brown seaweeds were collected from the Maharashtra coast of India, and their biochemical composition was evaluated. The moisture, protein, fat, carbohydrate, dietary fibre,and ash along with nutrient profile such as fatty acid, amino acid, mineral content, and heavy metals content in dry powder of seaweed Spatoglossum asperum, Stoecho spermum marginatum and Iyengaria stellata were analysed. The protein content was observed to be significantly higher (p